ROLE OF ANTIDEPRESSANTS IN AMENDING THE CHEMICAL DISPARITY OF NEUROTRANSMITTERS IN PSYCHOSOMATIC DISORDERS.: Role of Antidepressants in psychosomatic disorders - Agarwal, Mugdha; Agarwal, Shriya; Agarwal, Vinayak; ., Rachana; Singh, Manisha (Journal of Biomedical and Pharmaceutical Research, 2019)
This review summarizes the most common types of psychosomatic disorders including various types of depression based on their evolution, causes, symptoms and severity. The cellular and molecular mechanism behind the same in the areas of the brain, which are most susceptible to damage, both structurally and functionally (amygdala, the prefrontal cortex and the hippocampus) were keenly looked in to. Further, the therapeutic intervention through antidepressants was also been explored along with its three major categories in which they have been divided, their types, properties and mechanism of actions, especially towards the regulation of neurotransmitters in the brain has been highlighted. The behaviour of neurotransmitters in the presence of particular antidepressants is of grave importance in order to design an effective antidepressant drug, which could beat currently ineffective ones in the market and their potential forms have been studied and described. This review also provides an insight about the different approaches used for diagnosis using different types of biomarkers.